Deep fluid circulation within crystalline basement rocks and the role of hydrologic windows in the formation of the Truth or Consequences, New Mexico low‐temperature geothermal system. Issue 1 (7th October 2014) - Pepin, J.; Person, M.; Phillips, F.; Kelley, S.; Timmons, S.; Owens, L.; Witcher, J.; Gable, C.
Abstract Hot springs can occur in amagmatic settings, but the mechanisms of heating are often obscure. We have investigated the origin of the Truth or Consequences, New Mexico low‐temperature (approximately 41°C) hot springs in the southern Rio Grande Rift. We tested two hypotheses that could account for this amagmatic geothermal anomaly: lateral forced convection in a gently dipping carbonate aquifer and circulation through high‐permeability crystalline basement rocks to depths of 8 km that is then focused through an overlying faulted hydrologic window. These hypotheses were tested using a regional two‐dimensional hydrothermal model. Model parameters were constrained by calibrating to measured temperatures, specific discharge rates, and groundwater residence times. We collected 16 temperature profiles, 11 geochemistry samples, and 6 carbon‐14 samples within the study area. The geothermal waters are Na+/Cl−‐dominated and have apparent groundwater ages ranging from 5500 to 11 500 years. Hot‐spring geochemistry is consistent with water/rock interaction in a silicate geothermal reservoir, rather than a carbonate system. Peclet number analysis of temperature profiles suggests that specific discharge rates beneath Truth or Consequences range from 2 to 4 m year−1. Geothermometry indicates maximum reservoir temperatures are around 170°C. Observed measurements were reasonably reproduced using the deep circulation permeable‐basement modeling scenario (10−12 m2) but not the lateral forced‐convection carbonate‐aquifer scenario. Focused geothermal discharge is the result of localized faulting, which has created a hydrologic window through a regional confining unit. In tectonically active areas, such as the Rio Grande Rift, deep groundwater circulation within fractured crystalline basement may play a more prominent role in the formation of geothermal systems than has generally been acknowledged.